The Innovative Personality of Indonesia’s Cross-Generational Population in the Adoption of Investment Application Innovations - Triwijayati, Anna (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: The success of the diffusion of innovation is highly dependent on the speed of adoption by adopters. Adopters have individual innovative characteristics that determine the willingness to adopt new innovations. This study aims to analyze the differences in FFM across Generations X, Y, Z on the adoption of innovation mobile investment apps. Background Problems: The existence of digital consumers has led to consumer behaviour that relies on innovation and digital technology. Consumer innovativeness characteristics are related to consumption behaviour and adoption of innovations that are formed persistently and grow from childhood. Therefore, it is important to know the characteristics of innovation in Generation X, Y and Z in Indonesia. Research Methods: this research takes the form of survey research. The number of respondents was 88 people who installed investment mobile applications. The variable of this study is the Five Factor Model (FFM) which is one of the instruments measuring the characteristics of consumer innovation. There are 5 characteristic factors: Open to Experience (OE), Extraversion (EXT), conscientiousness (CSC), Agreeableness (AGR), and Neuroticism (NEU). The Data were analysed using ANOVA. Finding/Results: the results showed that there are differences in the components of the Five-factors of Personality, namely OE, CSC, AGR in Gen Y and Z; where Gen Y has a greater mean value. There is also a difference in OE between Gen X and Y, where Gen Y has a greater mean. There is a difference in NEU between Gen X and Z, where Gen Z has a greater mean. Conclusion:GenerationYis the most persistent generation and showsthe characteristics of FFM.This researchis usefulfor marketers in implementing communication strategies based on consumer personality and to seethe map of intergenerational consumer innovativenessin Indonesia becausetheyare the determinantsof the success of innovation diffusion.